Digital Marketing Strategy on Online Purchase Decision on TikTok Online Shopping Platform - Handayani, Eliya Hikmah; Rasidi, Moh. (Manunggal Halim Jaya, 2024)
This study aims to determine the factors that influence consumer purchasing decisions on TikTok shop and differences in TikTok shop compared to other e-commerce platforms. Using a descriptive qualitative approach, data were obtained through in-depth interviews, observation, and documentation of consumer actors in Sentul Village, Gading District, who use TikTok Shop as a shopping medium. The results show that creative content strategies, utilization of influencers, and the use of live streaming features significantly increase consumer buying interest, digital marketing has a significant effect, while influencers and online customer reviews have a positive effect on purchasing decisions.